General attitudes towards marriage scale: psychometric properties in Malaysian adolescents of divorced families - Fam, Jia Yuin; Yaacob, Siti Nor; Juhari, Rumaya; Arshat, Zarinah; Mukhtar, Firdaus (Springer, 2017)
Attitudes towards marriage in adolescence may influence the relationship quality in later years. There exist many measures of attitudes towards marriage which were validated among adolescents from two-parent family in the Western context. There is a need to validate measure of attitudes towards marriage in different countries. This study examined the psychometric properties of the Malay version of general attitudes towards marriage scale in a sample of 480 adolescents from divorced families in Malaysia. Exploratory factor analysis yielded a two-factor structure of general attitudes towards marriage scale, which explained for 60% of the variance. Additionally, the two-factor structure of general attitudes towards marriage scale demonstrated good fit to data in the confirmatory factor analysis (non-normed fit index = .941, comparative fit index = .958, root mean square error of estimation = .087, and χ 2/df = 4.615). Overall, the general attitudes towards marriage scale exhibited good internal consistency (α = .901), which supports the reliability of the instrument. The significant relationships between general attitudes towards marriage scale and other constructs also provided evidences to the convergent validity (r = .761, p < .001 with intent to marry, r = −.170, p < .001 with overt inter-parental conflict, and r = .523, p < .001 with mother–adolescent relationship). Significant gender difference was found in the report of general attitudes towards marriage scale (t = −2.265, p < .05). Thus, the translated general attitudes towards marriage scale is a reliable, valid, and practical instrument to measure attitudes towards marriage among Malaysian adolescents in divorced family setting.